The number of articles submitted to the Journal of the Faculty of Medicine experienced a dramatic increase (2017)
The Journal of the Faculty of Medicine of Universidad Nacional de Colombia has undergone important changes in the past years; the amount of articles submitted for initiating the editorial process has increased, in the same manner as the amount of articles received in English language, and the rejection rate, which is now around 40%. The number of international authors has also grown, thus demonstrating that the publication has achieved greater visibility and recognition.In this context, the following articles have been selected for the first issue of Volume 69 of the Journal of the Faculty of Medicine:“Is parricide a stable phenomenon? An analysis of parricide offenders in a forensic hospital” (1) is a study written by an important group of Brazilian authors, who demonstrate their expertise in one of the crimes that causes most social upheaval due to its broad implications. Parricide immediately attracts attention as it is easily linked to the presence of a mental disorder, which is actually corroborated by this study, since it shows that most parricides are young adult males, who have a low level of education, are single, with no criminal history and schizophrenic; in addition, few cases show antisocial personality disorders.